What prevents Portuguese SMEs from innovating? - Cordeiro, Ana (2012)
The importance of innovation on the survival and competitiveness of organizations is an undeniable fact. Small and Medium enterprises (SMEs) represent 99,99% of all Portuguese firms. This reality is shared by other European countries and therefore it is relevant to study their innovative behavior and attitudes in order to achieve competitiveness and sustainability. The present study inquires about barriers to innovation, namely, what are the barriers faced by domestic companies, which barriers are easier to recognize and overcome and what is the level of importance they have on the firm point of view. The course of the investigation consists primarily in undertaking literature review on topics such as innovation, barriers to innovation, SMEs, strategy and competitiveness. The theoretical support, resulting there from leads to the building line of work that is embodied in two surveys. The results achieved made possible the creation of two new models of classification and segmentation of the barriers. The BARINOV MODEL that evidences the existence of internal or external barriers and flashes upon the concept of deviation barrier. The BARIFASE MODEL embodies the innovation process through three phases and evidences the occurrence of the barriers to innovation during these stages.